Večrazsežnostno vrednotenje alternativ za primer dodatnega pokojninskega zavarovanja - Saražin Lovrečič, Ines (Uporabna informatika (Ljubljana), 1994)
In this paper we present multidimensional evaluation of alternatives from the viewpoint of insured person. We deal with the case of free-will extended coverage retirement insurance. A computer-aided method which equally incorporates both qualitative and quantitative elements into the process of decision-making is applied.
Keywords: informacijski sistemi; informatika; odločanje; pokojninsko zavarovanje; prostovoljno zavarovanje